FINANCIAL MANAGEMENT ARCHITECTURE NOT ASSOCIATED WITH THE BUSINESS COMPETENCE COEFFICIENT 3CA - Argota-Pérez, Yadira (2022)
The aim of the study was to evaluate the architecture of financial management not associated with the coefficient of business competence 3CA. Two organizations from Cuba and one from Peru were selected, where they were classified, in three center categories. Eight specific criteria of financial management were analyzed, as well as indicators of financial management from the coefficient of business competence 3CA. The cost of marketing channels and the level of indebtedness explained 99.92% of the variability between all the criteria. No statistically significant differences were found between the production organizations for the financial management values ​​in the competence of the entrepreneurial competence coefficient 3CA. The three organizations were statistically the same, but ESAC and DISAIC show very similar characteristics between them (dendrogram) compared to AMTAWI. The level of competition for the organizations was satisfactory and the order corresponded to: DISAIC > AMTAWI > ESAC. The correlation coefficient between the specific criteria of financial management and the indicators of the organizational competitiveness coefficient 3CA, indicated a weak relationship. It is concluded that the specific indicators of financial management are not associated with the indicators of the coefficient of business competence 3CA and this means an inadequate decision in organizational performance, therefore, it is required to integrate the specific indicators to the coefficient to show greater architecture. towards the dimension of competence and organizational visibility. Keywords: economic management – market analysis – organizational visibility – social control – strategic sustainability